Association between Maternal Body Mass Index and Neonatal Apgar Scores: A Multicenter Study - Ryan Haryana Darajatun; Aditiyono Aditiyono; Muhammad Alamsyah Aziz; Nurul Robiah Aladawiyah (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objective: To determine the association between maternal body mass index (BMI) and neonatal Apgar scores in two tertiary referral hospitals in Indonesia between 2023 and 2024.Methods: This cross-sectional study analyzed the medical records of 200 women who delivered at Dr. Hasan Sadikin Hospital, Bandung, and Prof. Dr. Margono Soekarjo Hospital, Purwokerto, from August 2023 to July 2024. Participants were classified based on maternal BMI. The associations between BMI, mode of delivery, and Apgar scores were analyzed using chi-square tests and logistic regression.Results: Maternal BMI, mode of delivery, age, parity, gestational age, and comorbidities showed no significant association with Apgar scores (p > 0.05). Birth weight was the only significant predictor; infants with low birth weight were associated with Apgar scores <7 (OR 0.219; 95% CI: 0.118–0.407). Regarding mode of delivery, 69.2% of obese mothers underwent cesarean section compared to 52.3% of normoweight mothers. Obese mothers were significantly more likely to have a cesarean delivery, although this did not correlate with lower Apgar scores.Conclusion: Maternal obesity is associated with a higher chance of cesarean delivery but does not significantly affect neonatal Apgar scores. Infant birth weight remains the strongest predictor of Apgar scores in this group. AbstrakTujuan: Penelitian ini bertujuan untuk mengetahui asosiasi antara indeks massa tubuh (IMT) dan skor Apgar dengan obesitas pada kehamilan di Rumah Sakit Margono dan Rumah Sakit Hasan Sadikin selama tahun 2023 – 2024.Metode: Penelitian ini merupakan studi observasional analitik dengan pendekatan potong lintang. Data diperoleh dari rekam medis 200 ibu bersalin periode Agustus 2023 – Juli 2024 di RSUP Dr. Hasan Sadikin Bandung dan RS Prof. Dr. Margono Soekarjo Purwokerto. Subjek diklasifikasikan berdasarkan Indeks Massa Tubuh (IMT). Hubungan antara IMT dengan metode persalinan dan skor Apgar dianalisis menggunakan uji chi-square dan regresi logistik.Hasil: Hasil penelitian menunjukkan bahwa dari seluruh variabel, hanya berat lahir bayi yang berpengaruh signifikan terhadap skor Apgar. Bayi dengan berat lahir rendah berisiko lebih tinggi mendapat skor Apgar rendah (p < 0,05) OR 0,219 (CI 95% 0,118–0,407). Tidak ditemukan hubungan signifikan antara IMT maupun metode persalinan dengan skor Apgar (p > 0,05). Persalinan seksio sesarea terjadi pada 52,3% ibu dengan IMT normoweight dan 69,2% pada kelompok obesitas. Kesimpulan: Obesitas pada ibu hamil meningkatkan risiko persalinan dengan seksio sesarea. Berat lahir bayi merupakan prediktor skor Apgar yang signifikan.